Reduction in polyamine catabolism leads to spermine‐mediated airway epithelial injury and induces asthma features. Issue 10 (29th October 2018) - Jain, V.; Raina, S.; Gheware, A. P.; Singh, R.; Rehman, R.; Negi, V.; Murray Stewart, T.; Mabalirajan, U.; Mishra, A. K.; Casero, R. A.; Agrawal, A.; Ghosh, B.
Abstract: Background: Airway epithelial injury is a crucial component of acute and severe asthma pathogenesis and a promising target for treatment of refractory asthma. However, the underlying mechanism of epithelial injury remains poorly explored. Although high levels of polyamines, mainly spermine, have been found in asthma and comorbidity, their role in airway epithelial injury and the cause of their altered levels in asthma have not been explored. Methods: We measured key polyamine metabolic enzymes in lung samples from normal and asthmatic subjects and in mice with OVA‐induced allergic airway inflammation (AAI). Polyamine metabolism was modulated using pharmacologic/genetic modulators. Epithelial stress and apoptosis were measured by TSLP levels and TUNEL assay, respectively. Results: We found loss of the polyamine catabolic enzymes spermidine/spermine‐N (1)‐acetyltransferase‐1 (SAT1) and spermine oxidase (SMOX) predominantly in bronchial epithelial cells (BECs) of human asthmatic lung samples and mice with AAI. In naïve mice, SAT1 or SMOX knockdown led to airway hyper‐responsiveness, remodeling, and BEC apoptosis. Conversely, in mice with AAI, overexpression of either SAT1 or SMOX alleviated asthmatic features and reduced TSLP levels and BEC apoptosis. Similarly, while pharmacological induction of SAT1 and SMOX using the polyamine analogue bis(ethyl)norspermine (BENSPM) alleviated asthmatic features with reduced TSLP levels and BEC apoptosis, pharmacological inhibition of these enzymes using BERENIL or MDL72527, respectively, worsened them. Spermine accumulation in lungs correlated with BEC apoptosis, and spermine treatment caused apoptosis of human BEAS‐2B cells in vitro. Conclusions: Spermine induces BEC injury. Induction of polyamine catabolism may represent a novel therapeutic approach for asthma via reversing BEC stress. Abstract : Polyamine catabolic enzymes, SAT1 and SMOX, are reduced in asthma. Polyamine accumulation contributes to increased bronchial epithelial fragility in asthma. Drugs or genetic modulation that increases polyamine catabolism are effective in models of asthma.